Synthesis and Characterization of Alumina Precursors Derived from Aluminum Metal through Electrochemical Method - Eva Marlina Ginting; Nurdin Bukit (Universitas Gadjah Mada, 2015)
This study investigated the use of the electrochemical method to prepare alumina (a-Al2O3) from aluminum metal. The a-Al2O3 precursor was calcined at 110 °C for six hours and then characterized using Fourier Transform Infrared (FTIR) spectroscopy, Particle Size Analysis (PSA), X-Ray Diffraction spectroscopy (XRD), and Scanning Electron Microscopy (SEM). To study transformation of the precursor into α-Al2O3, three samples were sintered at 400, 800, and 1200 °C, respectively and they were characterized. The most interesting result obtained was the transition of AlOOH and β-Al(OH)3 into γ-Al2O3 at low temperatures (400 to 800°C), followed by transformation of γ-Al2O3 into a-Al2O3 at high temperature (1200 °C). The overall results obtained demonstrated that electrochemical method is a potential alternative for production of α-Al2O3, which can be achieved in practically pure phase at sintering temperature at 1200 °C.